An Anthropometric Evaluation of Workstation Design: A Case Study in an Automotive Industry - Radin Zaid, Radin Umar; Nadiah, Ahmad; Isa, Halim (2008)
Awkward body postures in manual material handling have frequently been associated with high risks of occupational injuries. Anthropometrical issue such as reaching limits has often not been given enough consideration during workstation design process. The objectives of this paper are 1) to analyze the anthropometrical issue of a case study in an automotive industry 2) to suggest anthropometrical intervention to improve usability and reduce injury risks. Systematic observation techniques were applied and population accommodated before and after anthropometrical intervention was analyzed using percentiles equation. The result shows that the current job settings limit the number of workers capable of performing the job without awkward postures. Redesigning work using anthropometrical interventions suggest that more population will be capable of operating the job without awkward postures. As a result, injuries and musculoskeletal disorder are expected to be minimized.